Branding satisfaction in the airline industry: a comparative study of Malaysia Airlines and Air Asia - Wong, K.M.; Musa, G. (Academic Journals, 2011)
Brand is crucial in differentiating the superiority of products or services over others. This is an exploratory study examining the differences in brand satisfaction between Malaysian Airlines (full service airlines) and Air Asia (low cost airlines) in Malaysia. 350 usable questionnaires were obtained from respondents in the two main airlines terminals in Kuala Lumpur. Exploratory factor analysis revealed seven brand satisfaction dimensions which are tangibles, price, core service, reputation, publicity, word-of-mouth, and employee. Generally, respondents were not satisfied with all brand dimensions of both airlines. The level of brand dissatisfaction is also higher for Malaysian Airlines compared with Air Asia. Air Asia was perceived better than Malaysian Airlines in price, publicity, and word-of-mouth. On the other hand, Malaysian Airlines was perceived better in tangibles, core service, reputation, and employee. The paper highlights some of its theoretical, managerial and marketing implications to the development of airline industry.